Family Caregivers of Older Adults, 1999–2015: Trends in Characteristics, Circumstances, and Role-Related Appraisal. (16th June 2017) - Wolff, Jennifer L; Mulcahy, John; Huang, Jin; Roth, David L; Covinsky, Kenneth; Kasper, Judith D
Abstract: Purpose of Study: To assess trends in family caregiving between 1999 and 2015. Design and Methods: We construct nationally representative profiles of community-dwelling older adults receiving help with self-care or indoor mobility and their "primary" family or unpaid caregiver using the 1999 and 2004 National Long Term Care Survey, 2011 and 2015 National Health and Aging Trends Study, and linked caregiver surveys. Trends are examined. Results: Older adults receiving help were incrementally younger, more racially diverse, and better educated in 2015. Primary caregivers overwhelmingly continued to be spouses and adult children. Arrangements were increasingly 4 years or longer in duration (shifting from 44.8% in 1999 to 60.5% by 2015). On average, primary caregivers provided about or in excess of 30 hr per week at all four time points. Spouses provided fewer hours of care, were twice as likely to work, and half as likely to report substantial emotional, physical, and financial difficulty due to caregiving in 2015 than 1999. Adult children provided comparable hours of care to a more impaired population; a similar proportion reported substantial caregiving-related difficulty at each time. Use of respite care nearly doubled from 8.5% in 1999 to 15.7% in 2015. Dementia caregivers were less likely to report substantial physical and financial difficulty and more likely to use respite care in 2015 than 1999. Implications: Family caregivers' circumstances generally improved during the 16-year period. Results diverge from prevailing concerns regarding the state of family caregiving and demonstrate the importance of longitudinally monitoring trends in late-life family caregiving.